Aplicación de la educación tecnológica y su incidencia en la potenciación de destrezas con criterio de desempeño de los estudiantes del III bachillerato sistemas de la Unidad Educativa “Jaime Roldós Aguilera”, Cantón Montalvo, Provincia los Ríos. - Medrano Loor, Diana Carolina (2016)
The present research work entitled APPLICATION OF THE TECHNOLOGICAL EDUCATION AND ITS INCIDENCE IN THE POTENTIATION OF SKILLS WITH CRITERIA OF PERFORMANCE OF STUDENTS OF THE III BACHILLERATO SYSTEMS OF THE EDUCATIONAL UNIT" JAIME ROLDÓS AGUILERA ", CANTÓN MONTALVO, PROVINCE LOS RÍOS, Aims to determine the incidence of the application of technological education in the enhancement of skills with the performance criteria of students of the III Bachelor System of the Educational Unit "Jaime Roldós Aguilera, Canton Montalvo, Province Los Ríos. Descriptive and explanatory diagnostic research was used with the inductive-deductive method and its respective survey applied to teachers and students; With a sample of 35 participants. The results of the investigation identified the variables that intervene in the hypothesis and it was possible to verify each one of them through the Chi square declaring it true. Conclusions were established where the relationship of technology with education has a close union because it allows it to generate and enhance the abilities that the students possess and to contribute in the training and development of the skills with criterion of performance, but the teachers of the Unit Educativa Jaime Roldos Aguilera are not using technological tools that allow students to discover their skills according to a specific area of performance.